From Mystical Unveiling to Spiritual Therapy: Kasyf and the Reconstruction of Sufi Healing in the Syadziliyah - Sauqi, Achmad (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This article seeks to discuss of kasyf—the unveiling of inner truths—in the Syadziliyah Sufi healing practices of Tulungagung, Indonesia, focusing on santri experiences. Employing a phenomenological approach, data were gathered through observations and in-depth interviews with santri who have undergone kasyf. This article argues that kasyf significantly supports tazkiyatun nafs (self-purification) and enhances spiritual well-being. Notably, santri display differing levels of kasyf despite following the same zikir practices, highlighting its nature as a divinely bestowed experience rather than a structured objective. This sets Syadziliyah healing apart from other Sufi traditions, which often emphasize more systematic spiritual and psychological frameworks. The study also critiques Karim Mitha’s notion of “self-knowledge,” proposing “soul-knowledge”—an integrative framework combining self-knowledge and tazkiyatun nafs—to guide salik toward discovering the “true soul.” The research presents a novel model of transformative Sufi healing in the Syadziliyah tradition, emphasizing individualized spiritual experiences and the central role of divine grace in personal spiritual development.